The challenges of Virtual money “Bitcoin BTC” - Merrad, Rais (Dirassat Journal Economic Issue, 2019)
Our research topic covered the study of virtual money " Bitcoin " from economical point of view, which is used for e-commercial transactions through the internet, our work focused on what so called “virtual money "Bitcoin "as a means of electronic payments. The research concluded that: 1. the e-money, has two forms or generations, 1st is the e-money in the closed network and 2nd e-money of open network or crypto money 2. The research also discussed the risk of dealing with electronic money and its impact. 3. Finally, the research concluded with the effects of dealing with electronic money on some contemporary transactions.